The Jesuits and globalization : historical legacies and contemporary challenges - Banchoff, Thomas F. 1964- (Washington, D.C. Georgetown University Press, 2016)
The Society of Jesus, commonly known as the Jesuits, is the most successful and enduring global missionary enterprise in history. Founded by Ignatius Loyola in 1540, the Jesuit order has preached the Gospel, managed a vast educational network, and shaped the Catholic Church, society, and politics in all corners of the earth. Rather than offering a a global history of the Jesuits or a linear narrative of globalization, Thomas Banchoff and José Casanova have assembled a multidisciplinary group of leading experts to explore what we can learn from the historical and contemporary experience of the Society of Jesus?what do the Jesuits tell us about globalization and what can globalization tell us about the Jesuits? Contributors include comparative theologian Francis X. Clooney, SJ, historian John W. O'Malley, SJ, Brazilian theologian Maria Clara Lucchetti Bingemer, and ethicist David Hollenbach, SJ. They focus on three critical themes?global mission, education, and justice?to examine the historical legacies and contemporary challenges. Their insights contribute to a more critical and reflexive understanding of both the Jesuits'history and of our contemporary human global condition.
Keywords: Jesuitas -- Historia; Globalización -- Aspectos religiosos